2018
DOI: 10.3926/jiem.2467
|View full text |Cite
|
Sign up to set email alerts
|

Safety disconnect: Analysis of the role of labor experience and safety training on work safety perceptions

Abstract: Abstract:Purpose: This study analyzes work safety perceptions among workers and safety experts in the construction industry. Furthermore, we evaluate whether experiential learning (i.e., labor experience) and knowledge-enhancing practices, that we link to safety training, explain the differences in work safety perceptions of workers and safety experts by triggering different types of overconfidence biases.Design/methodology/approach: The proposed hypothesis are tested by applying ordered probit models on a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…Paragraf berikut beberapa penelitian yang dilakukan untuk melihat hubungan seberapa besar pelatihan dapat meningkatkan awareness pekerja sehingga berpengaruh terhadap kinerja keselamatan kerja secara keseluruhan. Lafuente, Abad, and Vaillant (2018) melihat hubungan antara pengalaman kerja, pelatihan aspek KKK yang pernah didapat dibandingkan dengan persepsi terhadap aspek Keselamatan. Pengalaman tenaga kerja sebelumnya memiliki efek yang signifikan terhadap keselamatan kerja yang dirasakan, yaitu justru kesadaran risiko menurun sehubungan dengan pengalaman kerja.…”
Section: Pendahuluanunclassified
“…Paragraf berikut beberapa penelitian yang dilakukan untuk melihat hubungan seberapa besar pelatihan dapat meningkatkan awareness pekerja sehingga berpengaruh terhadap kinerja keselamatan kerja secara keseluruhan. Lafuente, Abad, and Vaillant (2018) melihat hubungan antara pengalaman kerja, pelatihan aspek KKK yang pernah didapat dibandingkan dengan persepsi terhadap aspek Keselamatan. Pengalaman tenaga kerja sebelumnya memiliki efek yang signifikan terhadap keselamatan kerja yang dirasakan, yaitu justru kesadaran risiko menurun sehubungan dengan pengalaman kerja.…”
Section: Pendahuluanunclassified
“…The inclusion of safety management is a crucial aspect that should be prioritised by any organisation [2]. It plays a key role in enhancing the supervision of employees, minimising accidents, near misses and occupational injuries, while simultaneously enhancing overall business operations [3]. The continuous technological advances of today-the implementation of new work processes that take into account market needs and human capabilities-reinforce the need for worker safety [2].…”
Section: Introductionmentioning
confidence: 99%
“…The success of OSH training in shaping safe worker behaviour needs to be supported by management [5]. Nevertheless, findings from a study conducted by Lafuente et al [3] indicate that elevated levels of OHS training, when coupled with the acquisition of codified knowledge, have a detrimental impact on workers' safety perceptions. Interestingly, this effect appears to be positive for safety professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the success of a safety training program requires coordination of two key players, managers and workers, and the alignment of their perceptions towards similar goals in implementing an effective safety training program. Not surprisingly, several researchers have shown significant discrepancies between the perception of safety among the construction stakeholders [5] - [8]. For example, Gilkey et al, found that managerial perception is more optimistic towards the safety atmosphere of their projects compared to the factual perception reported by the frontline workers [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that the workers' safety perception is predominantly derived from taskspecific performances and their experiences. On the other hand, the safety managers acquire their safety knowledge and expertise mostly from the formal sources of training and education [5].…”
Section: Introductionmentioning
confidence: 99%